Spring piglets or autumn piglets? Negotiating the role of nature in the spaces and practices of raising piglets in Finland, c. 1910s–30s - Nikkilä, Eeva (Cambridge University Press, 2025)
This article examines the role of nature in Finnish pig production in the first decades of the 1900s by focusing on two distinct types of pigs, namely spring piglets and autumn piglets, who were raised in physical surroundings that changed with the seasons. I will investigate how different seasonal changes, such as temperature variations and availability of natural feeds, impacted the spaces and practices within which piglets were raised. This article also includes the analysis of how humans attempted to substitute for nature at times when natural benefits, such as warm weather or sunlight, were not available. Furthermore, I will analyse how the bodies and experiences of spring and autumn piglets reflected the different sets of circumstances in which they were raised. Broadly, this article examines how an animal production system negotiated its relations to nature and natural phenomena in the early stages of commercialization and modernization.